PENGEMBANGAN BAHAN AJAR BERORIENTASI KOMIK MATA PELAJARAN IPAS PADA SISWA KELAS IV SEKOLAH DASAR NEGERI 36 PONTIANAK KOTA - Wahyuni, Nunung; Halidjah, Siti; Firmansyah, Andang (Universitas Tanjungpura, 2025)
The objective of this study is to design comic-oriented instructional materials for IPAS subjects intended for fourth-grade elementary school students, which has been validated by subject matter experts and design experts, as well as to determine its level of practicality based on responses from teachers and students. The research employed a Research and Development (R&D) method using the ADDIE model, although it was only conducted up to the implementation stage. The limited implementation involved 15 students from class IVA at SD Negeri 36 Pontianak Kota. Data collection instruments included validation sheets by subject matter and design experts, along with feedback questionnaires from teachers and students. The validation results from the subject matter expert yielded a feasibility score of 100%, while the design expert provided a score of 94%, indicating that the teaching material is highly feasible for use. Teacher responses showed a practicality percentage of 94.64%, and student responses reached 85.33%, both of which fall into the